2018
DOI: 10.1002/2017jb015114
|View full text |Cite
|
Sign up to set email alerts
|

An Active Seismic Zone in Intraplate West Iberia Inferred From High‐Resolution Geophysical Data

Abstract: Intraplate Iberia is a region of slow lithopsheric deformation (<1 mm/yr) with significant historical earthquake activity. Recent high‐quality instrumental data have shown that small‐magnitude earthquakes collapse along clusters and lineaments, which however do not bear a clear relationship to geologically mapped active structures. In this article, we investigate the controls of these earthquake clusters. In particular, we study two of the identified clusters—the Arraiolos and the Évora seismic zones (ASZ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 170 publications
1
7
1
1
Order By: Relevance
“…region. This has been exemplified in a previous study of seismicity in Alentejo (southern Portugal) by Matos et al (2018). This study showed that epicentral locations calculated with PRISM3D, using NonLinLoc to compute traveltimes on a full 3-D grid, could be shifted by up to ∼10 km with respect to those obtained with the IGN 1-D model.…”
Section: Impact On Traveltimessupporting
confidence: 70%
“…region. This has been exemplified in a previous study of seismicity in Alentejo (southern Portugal) by Matos et al (2018). This study showed that epicentral locations calculated with PRISM3D, using NonLinLoc to compute traveltimes on a full 3-D grid, could be shifted by up to ∼10 km with respect to those obtained with the IGN 1-D model.…”
Section: Impact On Traveltimessupporting
confidence: 70%
“…Those faults are approximately perpendicular to the faults proposed in this study and most likely related to Mesozoic rifting. Thus, they are not necessarily contradictory to the results of our analysis especially when considering the world stress data (Heidbach et al, 2016;Stich et al, 2020) and GNSS data (Matos et al, 2018;Palano et al, 2015) in the propsosed source area. Our findings, the missing geological evidence, and the ambiguities in the proposed source zone require further field investigation.…”
Section: Discussioncontrasting
confidence: 46%
“…The stations were oriented with magnetic compass. The array is situated on metamorphic rocks of neoproterozoic and lower palaeozoic age of the Ossa Morena zone near the seismically active east-west striking Moura-Vidigueira fault and the longer Messejana fault striking NE-SW (Borges et al 2001;Matos et al 2018). A few focal mechanisms obtained for this area show strike-slip characteristics (Borges et al 2001).…”
Section: Data a N D L O C A L S I T E C O N D I T I O N Smentioning
confidence: 99%